Decidual Granulomata of Unclear Significance. (October 2020) - Raj, Thomas; Pierce, Brian; Brady, Robert
Granulomatous inflammation is a histologic finding with a relatively wide variety of causes. In general, considerations include infectious etiologies, autoimmune conditions, or foreign body reactions. Granulomatous inflammation is uncommonly seen in the placenta. We present a unique case of a young woman with preterm labor and rupture of membranes whose placenta demonstrated perivascular decidual granulomata in the membranes and the basal plate.